Sarcopenia and systemic inflammation are associated with decreased survival after cytoreductive nephrectomy for metastatic renal cell carcinoma. Issue 11 (14th March 2022) - Khan, Amir Ishaq; Psutka, Sarah P.; Patil, Dattatraya H.; Hong, Gordon; Williams, Milton A.; Bilen, Mehmet A.; Sekhar, Aarti; Kissick, Haydn T.; Narayan, Vikram M.; Joshi, Shreyas S.; Ogan, Kenneth; Master, Viraj A.
Abstract : Background: This study was aimed at assessing the associations of sarcopenia, muscle density, adiposity, and inflammation with overall survival (OS) after cytoreductive nephrectomy (CN) for metastatic renal cell carcinoma. Methods: In all, 158 patients undergoing CN from 2001 to 2014 had digitized preoperative imaging for tissue segmentation via Slice‐O‐Matic software (version 5.0) at the mid‐L3 level. The skeletal muscle index was calculated with the skeletal muscle area (cm 2 ) normalized for height (m 2 ), and the skeletal muscle density (SMD) was calculated with average Hounsfield units. Adiposity was measured with the cross‐sectional area (cm 2 ) of visceral, subcutaneous, and intramuscular adiposity compartments and was similarly normalized for height. The average fat density was obtained in Hounsfield units. OS was estimated with the Kaplan‐Meier method. Associations between body composition, inflammation metrics, and relevant clinicopathology and OS were assessed with univariable and multivariate Cox analyses. Results: Seventy‐six of the 158 patients (48%) were sarcopenic. Sarcopenia was associated with elevated neutrophil to lymphocyte ratios (NLRs; P = .02), increased age ( P = .001), lower body mass indices ( P = .009), greater modified Motzer scores ( P = .019), and lower SMD ( P = .006). The median OS was 15.0 and 29.4 months for sarcopenic and nonsarcopenic patients, respectively ( P = .04). Elevated inflammation (NLR or C‐reactive protein), in addition to sarcopenia, was independently associated with OS, with an elevated NLR ≥ 3.5 and sarcopenia associated with the poorest OS at 10.2 months. No associations were observed between measurements of muscle density or adiposity and OS. Conclusions: Sarcopenia and measures of high systemic inflammation are additively associated with inferior OS after CN and may be of use in preoperative risk stratification. Lay Summary: Body composition and sarcopenia (a deficiency in skeletal musculature) have been shown to affect outcomes in cancer. We found that sarcopenic patients had poor survival in comparison with nonsarcopenic patients in the setting of metastatic renal cell carcinoma (mRCC). Patients with both elevated inflammation and sarcopenia had the poorest survival. Sarcopenia is an objective measure of nutrition that can assist in therapeutic counseling and decision‐making for individualized treatment in mRCC. Abstract : Sarcopenia and measures of high systemic inflammation are additively associated with inferior overall survival after cytoreductive nephrectomy. This may be of use in preoperative risk stratification.